2010
DOI: 10.1105/tpc.109.067280
|View full text |Cite
|
Sign up to set email alerts
|

EOBII, a Gene Encoding a Flower-Specific Regulator of Phenylpropanoid Volatiles' Biosynthesis in Petunia  

Abstract: Floral scent, which is determined by a complex mixture of low molecular weight volatile molecules, plays a major role in the plant's life cycle. Phenylpropanoid volatiles are the main determinants of floral scent in petunia (Petunia hybrida). A screen using virus-induced gene silencing for regulators of scent production in petunia flowers yielded a novel R2R3-MYB–like regulatory factor of phenylpropanoid volatile biosynthesis, EMISSION OF BENZENOIDS II (EOBII). This factor was localized to the nucleus and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
207
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(225 citation statements)
references
References 60 publications
(111 reference statements)
8
207
0
2
Order By: Relevance
“…Phylogenetically, FaEOBII shares high amino acid homology with members of this subgroup of MYB TFs from other plants, such as PsMYB26 (Pisum sativum), NlxNsMYB305 (Nicotiana langsdorffii 3 Nicotiana sanderae), AmMYB305 (Antirrhinum major), AmMYB340 (A. major), AtMYB24 (Arabidopsis), AtMYB21 (Arabidopsis), and PhEOBII (petunia). Functional characterization of all of these TFs has demonstrated that they are involved in the regulation of the volatile benzenoid phenylpropanoid metabolic pathway (Sablowski et al, 1994;Moyano et al, 1996;Uimari and Strommer, 1997;Shin et al, 2002;Li et al, 2006;Liu et al, 2009;Spitzer-Rimon et al, 2010). All of these bioinformatic analyses suggested that FaEOBII could be an R2R3 MYB TF potentially involved in the regulation of those metabolic pathways related to volatile phenylpropanoid production in ripe receptacles.…”
Section: Sequence Analysis Of the Faeobii Gene And Proteinmentioning
confidence: 99%
See 4 more Smart Citations
“…Phylogenetically, FaEOBII shares high amino acid homology with members of this subgroup of MYB TFs from other plants, such as PsMYB26 (Pisum sativum), NlxNsMYB305 (Nicotiana langsdorffii 3 Nicotiana sanderae), AmMYB305 (Antirrhinum major), AmMYB340 (A. major), AtMYB24 (Arabidopsis), AtMYB21 (Arabidopsis), and PhEOBII (petunia). Functional characterization of all of these TFs has demonstrated that they are involved in the regulation of the volatile benzenoid phenylpropanoid metabolic pathway (Sablowski et al, 1994;Moyano et al, 1996;Uimari and Strommer, 1997;Shin et al, 2002;Li et al, 2006;Liu et al, 2009;Spitzer-Rimon et al, 2010). All of these bioinformatic analyses suggested that FaEOBII could be an R2R3 MYB TF potentially involved in the regulation of those metabolic pathways related to volatile phenylpropanoid production in ripe receptacles.…”
Section: Sequence Analysis Of the Faeobii Gene And Proteinmentioning
confidence: 99%
“…This suggests that these genes could be regulated by the synergistic action of EOBII and other TFs. On the other hand, PAL, CFAT, and IGS transcripts were up-regulated, indicating a direct positive regulatory role of the expression of these genes by EOBII (Spitzer-Rimon et al, 2010). Besides, ODO1 was demonstrated to activate the promoter of 5-ENOL-PYRUVYLSHIKIMATE-3-PHOSPHATE SYNTHASE (EPSPS), hence regulating the floral shikimate pathway that produces benzenoid/ pheylpropanoid volatiles (Verdonk et al, 2005).…”
mentioning
confidence: 94%
See 3 more Smart Citations